Toxicity Test Using The Brine Shrimp Lethality Test (BSLT) Method on Extracts of Stem Bark, Stem Wood, and Leaves on Bayur (Pterospermum diversifolium B. Rob.) - Zakaria Zakaria; Nunuk Hariani Soekamto; Nasriadi Dali; Hilda Ayu Melvi Amalia; Syamsidar Haji Syarifuddin (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2024)
Abstract: Ethnobotanically, the leaves of P. diversifolium are used as a medicine for itching and the root bark is used as fish poison. The traditional use of natural materials should be followed by scientific studies. This study aims to determine the toxicity of the stem bark, stem wood, and leaf tissue extracts of P. diversifolium using the Brine Shrimp Lethality Test (BSLT) method. Extraction using maceration method with ethanol solvent for 3 x 24 hours. The macerate was filtered and the extract obtained was evaporated until a crude extract was obtained. The three ethanol extracts obtained were tested for toxicity and obtained LC50 values of stem bark = 4,753 ppm, stem wood = 97,723 ppm, and leaves = 27,797 ppm. All extracts were declared non-toxic because the LC50 value was more than 1000 ppm.Abstrak: Secara etnobotani, daun P. diversifolium digunakan sebagai obat gatal serta kulit akarnya sebagai racun ikan. Penggunaan bahan alam secara tradisional seharusnya diikuti kajian ilmiah. Penelitian ini bertujuan untuk mengetahui toksisitas pada ekstrak jaringan kulit batang, kayu batang, dan daun P.diversifolium dengan metode Brine Shrimp Lethality Test (BSLT). Ekstraksi menggunakan metode maserasi dengan pelarut etanol selama 3 x 24 jam. Maserat disaring dan ekstrak yang peroleh dievaporasi sampai didapatkan ekstrak kental. Ketiga ekstrak etanol yang diperoleh diuji toksisitasnya dan diperoleh nilai LC50 kulit batang = 4.753 ppm, kayu batang = 97.723 ppm, dan daun = 27.797 ppm. Semua ekstrak dinyatakan tidak toksik karena nilai LC50 lebih dari 1.000 ppm.